Kearifan Lokal Minangkabau: Simbiosis Sosial Ekonomi Antara Pasar Nagari dengan Terminal di Sumatera Barat - Abbas, Ardi; Putra, Rinaldi Eka (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
Abstract: Market and terminal are two places that can both be described as something crowded, noisy, complicated, and prone to crime. However, behind this general condition, it turns out that markets and terminals are inseparable symbiosis in the economy of cities and regions. If this symbiosis is separated, inevitably, the terminal will not develop. This is the case with several inter-provincial (AKDP) and inter-provincial (AKAP) public transportation terminals. This paper explains the relationship between the two as a socio-economic symbiosis, a Minangkabau local wisdom, and the following phenomena. It can be concluded that (a). reflecting on the planning and development of traditional markets in West Sumatra, especially the nagari market; the nagari market is crowded because one is always next to the terminal (b). local wisdom between the market and the terminal is like water and fish. Fish cannot live without water. But a terminal without a market around it is like a fish without water. This is the case in nine of the ten AKDP and AKAP terminals in West Sumatra (c). terminal construction is always located in the district's capital city, except for the Kiliran Jao terminal (Sijunjung Regency), which does not consider the location's economic, pathological, and sociological aspects. However, each development is always accompanied by a feasibility study per the Ministry of Transportation requirements.